2007
DOI: 10.1038/ng2048
|View full text |Cite|
|
Sign up to set email alerts
|

Variation in FTO contributes to childhood obesity and severe adult obesity

Abstract: We identified a set of SNPs in the first intron of the FTO (fat mass and obesity associated) gene on chromosome 16q12.2 that is consistently strongly associated with early-onset and severe obesity in both adults and children of European ancestry with an experiment-wise P value of 1.67 x 10(-26) in 2,900 affected individuals and 5,100 controls. The at-risk haplotype yields a proportion of attributable risk of 22% for common obesity. We conclude that FTO contributes to human obesity and hence may be a target for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

80
1,184
9
35

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,440 publications
(1,308 citation statements)
references
References 11 publications
80
1,184
9
35
Order By: Relevance
“…FTO is well recognized for its strong association with increased body mass and obesity 52, 53. Given that obesity is a well‐established risk factor for a wide range of cancers, it is reasonable to postulate that FTO is intimately linked to cancers.…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 99%
“…FTO is well recognized for its strong association with increased body mass and obesity 52, 53. Given that obesity is a well‐established risk factor for a wide range of cancers, it is reasonable to postulate that FTO is intimately linked to cancers.…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 99%
“…42,43 Recent research is increasingly quantifying the effect of specific genotypes on metabolism or adiposity, with several of these associated with appetite regulation. 3,[44][45][46] Again, these appetite genes may have particular importance for offspring growth rather than adult phenotype. 47 However, the individual effects of these genes are of modest magnitude, hence the genetic basis of variation in adiposity manifests as their composite effect.…”
Section: The Generic Profile Of Thrift In Homo Sapiensmentioning
confidence: 99%
“…Genome‐wide association studies have identified obesity‐associated single nucleotide polymorphisms (SNPs) in a 47kb block of linkage disequilibrium (LD block) at the end of FTO intron 1 (Dina et al ., 2007; Frayling et al, 2007). As a result, FTO was thought to be the causal gene whose function was associated with weight gain (Fawcett and Barroso, 2010).…”
Section: Introductionmentioning
confidence: 99%